Significance of Glutathione Peroxidase 1 and Caudal-Related Homeodomain Transcription Factor in Human Gastric Adenocarcinoma - Jing Jing Han; De Rong Xie; Li Li Wang; Ye Qing Liu; Gong Fa Wu; Qing Sun; Yan Xian Chen; Ying Wei; Zhi Quan Huang; Hai Gang Li (Gastroenterology Research and Practice)
Aim. To investigate the expressions of glutathione peroxidase 1 (GPX1) and caudal-related homeodomain transcription factor (CDX2) in GAC and their correlation with clinicopathological features and tumor cell proliferation. Methods. The expressions of GPX1, CDX2, and Ki67 were immunohistochemically evaluated in 172 GAC specimens. The association of GPX1 and CDX2 with patient’s clinicopathological features and Ki67 positive rate was analyzed statistically. Results. In 172 cases of GAC, the expression of GPX1 was weaker than that in adjacent normal mucosa, and the expression of CDX2 was higher than that in adjacent normal mucosa. High expression GPX1 strong-expression was associated with differentiation, Lauren type, WHO type and extensive lymph node metastasis of GAC. High expression of CDX2 was associated with differentiation, Lauren type, WHO type, extensive lymph node metastasis, and TNM of GAC. Survival curves showed that expressions of GPX1 and CDX2 were factors of good outcome ( and .02, resp.). According to multivariate analysis, only lymph node metastasis, TNM stage, and CDX2 expression were independently associated with survival. In addition, a strong association of GPX1 expression was noted with Ki67 and CDX2. Conclusions. The expression of GPX1 and CDX2 may play a role in the carcinogenesis, differentiation, and progression of GAC, and CDX2 may be an independent prognostic factor.